Successful management of a delayed presented button battery ingestion in a toddler: A case report and literature review - Ebrahimi, Pouya; Nazari, Roozbeh; Mousavinezhad, Seyedeh Maryam; Senobari, Nahid; Ghadimi, Delaram J. (Clinical case reports, 2024)
Key Clinical Message It is important to note that prevention of button battery ingestion is the most effective way to reduce its incidence and complications. This is unachievable without providing educational plans for parents. Moreover, triage nurses and first‐line staff who take the history of patients and physicians should take the history to evaluate the risk of battery ingestion. Plain radiographs can be helpful in this matter, as the presence of “Hallow” and “Steep” signs in the anteroposterior and lateral views, respectively, can help. Foreign body ingestion is a relatively common occurrence in pediatrics, especially among children 1–3 years of age. Although most cases are benign and managed conservatively, those with high‐risk subjects such as button batterie can bring about fatal conditions in the minority of cases. In the present study, the history, diagnostic, and therapeutic procedures of a 13‐month‐old baby with the final diagnosis of button battery ingestion are presented. The parents ignored the symptoms, suspecting that it was a viral infection. The evaluations showed that a battery was lodged in the middle part of the thoracic esophagus, which was removed by an urgent endoscopic procedure. The patient was under observation and on a nothing‐by‐mouth diet for a week, receiving nutritional fluid with a nasogastric tube. The necrosis, which was obvious after the removal of the battery, was healing in the second control esophagogastroduodenoscopy performed 1 week after the procedure. The stricture was minimal, and no need for dilation was diagnosed. This case report underscores the importance of a timely diagnosis and removal of these cases. This case underscores the importance of the timely presentation of these cases to health care and the risk of delayed removal, such as necrosis, forming fistula, and perforation of the esophagus. The delay can cause necrosis, fistula, and perforation and might lead to irreversible severe complications and even death. Chest x‐ray shows the battery's position in esophagus.